Culture in Shaping the Disciplined Character of Santri Trough Punishment and Reward Methods at Pondok Pesantren Miftakhul Huda Nuruddin Ciomas Serang Banten - Saefudin Zuhri; Rizkiya Imamul Mahbubi (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
Abstract.Pondok Pesantren which is one of the non-formal institutions certainly plays a role in shaping the disciplined character of students aged students. One of the efforts made by Pondok Pesantren is to apply punishment and reward methods. The application of punishment and reward in Pondok pesantren certainly has a different style from punishment and reward in other educational institutions. The punishment and reward methods used in Pondok Pesantren are based on Islamic moral values. The purpose of this study was to determine the implications of the form of punishment and reward in the Pondok PesantrenMiftakhul Huda Nurruddin Ciomas. In this research process, the researcher used a descriptive qualitative method. Data was collected by observation, interviews, and documentation. From the results of this study, it can be concluded that the application of punishment in thePondok Pesantren Miftahul Huda Nuruddin is in the form of punishments such as writing istighfar, being whipped with a rattan, being shaved, reading out mistakes in public, apologizing to the Pondok Pesantrenleader, and being expelled from the Islamic boarding school. While the implementation of the reward program is carried out every 2 months with the form of rewards in the form of material and non-material. For example, rewards in the form of material, namely food and gifts in the form of stationery or other student needs. For non-material rewards, this is in the form of praise, motivational speech, and so on.